2016
DOI: 10.1111/hiv.12413
|View full text |Cite
|
Sign up to set email alerts
|

Very low level viraemia and risk of virological failure in treated HIV‐1‐infected patients

Abstract: In our population of HIV-infected patients on ART who achieved viral suppression at < 20 copies/mL, the risk of virological failure was no different for patients who remained fully suppressed compared with those who experienced subsequent episodes of VLLV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
1
15
4
2
Order By: Relevance
“…Multiple potential factors could explain these differences, including different ART regimens and frequency of testing 6 . However, because of the strict definition of VF used in this study, the occurrence of VF was substantially lower than previous reported data on both resource-rich regions 38,39 and resource-limited regions 2,7 . In a recent study from South Africa, 26% VF according to standard of WHO (VL > 1000 copies/ml once) showed spontaneous control of viral replication without changing treatment regimen, and therefore should not be considered as true VF 2 .…”
Section: Discussioncontrasting
confidence: 74%
“…Multiple potential factors could explain these differences, including different ART regimens and frequency of testing 6 . However, because of the strict definition of VF used in this study, the occurrence of VF was substantially lower than previous reported data on both resource-rich regions 38,39 and resource-limited regions 2,7 . In a recent study from South Africa, 26% VF according to standard of WHO (VL > 1000 copies/ml once) showed spontaneous control of viral replication without changing treatment regimen, and therefore should not be considered as true VF 2 .…”
Section: Discussioncontrasting
confidence: 74%
“…Multiple potential factors could explain these differences, including different ART regimens and frequency of testing [6]. However, because of the strict definition of VF used in this study, the occurrence of VF was substantially lower than previous reported data on both resource-rich regions [38,39] and resource-limited regions [2,7]. In a recent study from South Africa, 26% VF according to standard of WHO (VL > 1000 copies/ml once) showed spontaneous control of viral replication without changing treatment regimen, and therefore should not be considered as true VF [2].…”
Section: Discussionmentioning
confidence: 62%
“…The majority of the participants were male (92.9%, 2001/2155), with a Fig. 1 Flowchart showing selection of the participants median age at HIV diagnosis of 37 years old (IQR: [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. They mainly comprised of the Han nationality (85.4%).…”
Section: Characteristics Of Participants In This Studymentioning
confidence: 99%
“…Consequently, patients with LLV may be at increased risk of virological failure [15–21]. However, other investigators have failed to identify such an association [22, 23], and the level of viremia at which the risk of virological failure becomes significant remains controversial.…”
Section: Introductionmentioning
confidence: 99%